2000
DOI: 10.1128/aac.44.11.3092-3096.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Recombinant Human-Derived Pneumocystis carinii Dihydrofolate Reductase

Abstract: Dihydrofolate reductase (DHFR) is the target of trimethoprim (TMP), which has been widely used in combination with sulfa drugs for treatment and prophylaxis of Pneumocystis carinii pneumonia. While the ratderived P. carinii DHFR has been well characterized, kinetic studies of human-derived P. carinii DHFR, which differs from rat-derived P. carinii DHFR by 38% in amino acid sequence, have not been reported to date. Here we report on the expression and kinetic characterization of the recombinant human-derived P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…The DHFR nucleotide sequence was identical in 37 isolates from 35 patients except one with a single synonymous change, despite prior exposure to TMP in 15 patients [11]. Consistently, TMP was reported to be a poor inhibitor of P. carinii DHFR compared with the inhibition by other agents [14][15][16]. The present study found four substitution sites with two non-synonymous and two synonymous changes in the coding region of DHFR.…”
Section: Discussionsupporting
confidence: 66%
“…The DHFR nucleotide sequence was identical in 37 isolates from 35 patients except one with a single synonymous change, despite prior exposure to TMP in 15 patients [11]. Consistently, TMP was reported to be a poor inhibitor of P. carinii DHFR compared with the inhibition by other agents [14][15][16]. The present study found four substitution sites with two non-synonymous and two synonymous changes in the coding region of DHFR.…”
Section: Discussionsupporting
confidence: 66%
“…Although TMP-SMX is still the most effective first-line therapy, more than one-third of patients experience dose-limiting toxicity (1)(2)(3)(4)(5)(6). Failure of therapy or prophylaxis with TMP is common, but attempts to link these failures to variants of P. jirovecii dihydrofolate reductase (pjDHFR) that lead to alternative forms of the enzyme have been inconclusive (7,8). To date, most structural and drug design efforts have focused on the DHFR from Pneumocystis carinii (pcDHFR), the organism originally isolated from rat lungs (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…As discussed in the introduction, TMP-SMZ is used prophylactically for Pneumocystis pneumonia, despite the weak affinity of TMP for Pneumocystis DHFR (IC 50 ϭ 4.8 M for P. jirovecii DHFR) (18). Since the propargyl-based antifolates are significantly more potent than TMP against the fungal C. glabrata DHFR, they may also be effective against the fungal Pneumocystis DHFR.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, studies have reported that mutations conferring resistance to TMP-SMZ arise in DHPS, not in DHFR (17,28). In contrast, when the DHFR inhibitor pyrimethamine, which is four times more potent than TMP (18), is used in combination with sulfadiazine against pneumocystis, mutations arise in DHFR as well as DHPS (20). A logical conclusion of these studies is that the low potency of TMP against P. jirovecii DHFR is preventing it from reaching its full potential as an effective therapy for this eukaryotic opportunistic pathogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation